A detailed experimental and computational study of Cd complexes with pyridyl-based thiazolyl hydrazones - UĞUZ NELİ, ÖZLEM; KOCA, ATIF (My University, 2022)
Interest in Cd complexes has been growing in recent years. Cd complexes are considered a potential solution in the search for novel antibiotics that can fight antimicrobial resistance. In addition, Cd complexes draw attention to material chemistry. The main objective of this work was to prepare the first Cd(II) complexes with anionic forms of pyridine-based thiazolyl hydrazone (THs) ligands HLS2 [(E)-4-(4-methoxyphenyl)-2-(2-[pyridine-2-ylmethylene]hydrazinyl)thiazole] and HLS3 [(E)-2-(2-[pyridine-2-ylmethylene]hydrazinyl)-4-(p-tolyl)thiazole] and perform their structural and spectroscopic characterization, as well as stability in solution and upon heating. Studies related to their biological activities and possible electrochromic applications are also being conducted. Complexes [Cd(HLS2)(2)] (1) and [Cd(HLS3)(2)] (2) have been characterized by a single-crystal X-ray diffraction and computational analysis of intermolecular interactions responsible for their solid-state structures was performed. Thermal stability of 1 and 2 in the solid-state was analyzed by TGA/MS, where as their solution stability was determined by the spectrophotometric titration method. Electrochemical and in situ UV-Vis spectroelectrochemical analyses of 1 and 2 were carried out to determine redox mechanisms and the influence of the substituents and electrolytes on their redox responses. The antioxidant capacity of both complexes was tested in antioxidant assays, while their antimicrobial activity was tested against five Gram-positive and four Gram-negative bacteria, as well as against three fungi. The obtained results indicate their potent antioxidant capacity. The antimicrobial activity of investigated compounds on almost all tested bacterial strains was stronger than that of the standard antibiotic erythromycin. The results of docking studies indicate that the minor groove DNA is the possible biological target of 1 and 2.
Keywords: Kimya; İnorganik Kimya; Diğer; Temel Bilimler; Chemistry; Inorganic Chemistry; Other; Natural Sciences; KİMYA, UYGULAMALI; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); CHEMISTRY, INORGANIC & NUCLEAR; İnorganik kimya; Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Physical Sciences; antimicrobial activity; Cd(II) complex; docking; in situ spectroelectrochemistry; thiazolyl hydrazones; COORDINATION POLYMER; CRYSTAL-STRUCTURE; INTERMOLECULAR INTERACTIONS; ANTIMICROBIAL ACTIVITY; PALLADIUM(II) COMPLEX; CD(II) COMPLEXES; LIGAND SYNTHESIS; IN-SITU; CADMIUM; PHOTOCHROMISM